Compact Computational Holographic Display - Chen, Ni; Wang, Congli; Heidrich, Wolfgang (Frontiers in Photonics, 2022)
Holographic display is the ultimate three-dimensional (3D) display technique because it can produce the wavefront of the 3D objects. The dynamic holographic display usually requires a spatial light modulator (SLM) with a following 4f system to eliminate the unnecessary orders produced by the grating structure of the SLM. We present a technique that displays the images without the 4f system. We detect the unnecessary wavefield by phase-shifting holography and suppress it using computational optimization. Experimental results are presented to verify the proposed method.